Clinical utility of postmortem microcomputed tomography of the fetal heart: diagnostic imaging vs macroscopic dissection. (2nd December 2015) - Hutchinson, J. C.; Arthurs, O. J.; Ashworth, M. T.; Ramsey, A. T.; Mifsud, W.; Lombardi, C. M.; Sebire, N. J.
ABSTRACT: Objectives: Congenital cardiac malformations are commonly identified at perinatal autopsy, which can be challenging in fetuses of early gestation and in macerated fetuses. Our objective was to examine fetal complex congenital heart disease by microcomputed tomography (micro‐CT), using standard autopsy as the gold standard. Methods: In this ethically approved study, ex‐vivo isolated fetal heart and fetal heart‐lung blocks underwent iodine preparation prior to micro‐CT, and were fixed in formalin after the micro‐CT examination. Images were acquired using a microfocus‐CT scanner with individual specimen image optimization. Twenty‐one indices assessed normally at autopsy were evaluated for each dataset. Cardiac dissection was performed using a dissecting microscope within 24 h of the micro‐CT examination. Results: We examined six fetal hearts, comprising five with complex congenital cardiac malformations at a gestational age of 17–23 weeks and an anatomically normal heart of 23 weeks' gestation for reference. All specimens demonstrated excellent internal contrast at micro‐CT examination, and the correct overall diagnosis was made in all cases. There was agreement for 114/126 indices assessed on micro‐CT and at autopsy dissection (overall concordance of 95.8% (95% CI, 90.5–98.2%)). Micro‐CT was particularly useful in the assessment of ventricular morphology in macerated fetuses. Conclusions: Micro‐CT of small ex‐vivo fetal specimens can provide highly accurate three‐dimensional rendering of complex congenital fetal heart disease. This approach represents a significant advance in postmortem imaging and confirms the potential of this technology for non‐invasive examination of small fetuses and organs. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.